Conceptual design of pre-flood warning system based on user mobility - Mastor, F.A. (Institute of Electrical and Electronics Engineers Inc., 2016)
The occurrence of flood causes millions of damages, along with the loss of life and property and the devastation of agricultural and livestock. Therefore, an effective pre-flood warning system must be developed to mitigate flood losses and lessen the flood effects. However, when developing a warning system for flood disaster, limited communication during the occurrence and the availability of electricity should be taken into account. Thus, this paper proposes a conceptual framework with three (3) stages that consist of monitoring water level with reference to previous flood cases to determine flood danger status, alerting communities, passersby and local authorities regarding the water level and flood danger status and lastly is to notify flood victims to immediately go to the nearest relief center. By having an effective real time pre-flood warning system, immediate action can be carried out in order to save lives and minimize the damage caused by flood disaster. Â© 2015 IEEE.